Housing tenure, health and public healthcare coverage in Ireland - Harry Humes; Michelle Barrett; Brendan Walsh (The Economic and Social Research Institute (ESRI), 2023)
Housing and health are regarded as pressing concerns for the general public and policymakers in Ireland, but little information exists regarding their relationship. This study utilises data from the EU Survey on Income and Living Conditions (EU-SILC) to examine the correlations between housing tenure (homeowners, private renters or supported renters), health and healthcare coverage in Ireland. Furthermore, the research examines the evolution of these relationships over time and analyses the differences in self-reported health, chronic illness and medical card coverage across key socio-economic dimensions. We find significant variations in health and healthcare coverage across tenure groups. In general, supported renters have the poorest health outcomes, particularly those who are older and unemployed. These groups also have the highest levels of public healthcare coverage. However, a significant proportion of supported renters - especially those who are young and employed - do not hold a medical card. These individuals are at high risk of poverty and have low enough incomes to qualify for public housing assistance, yet may be left with a large financial burden in the event of a health emergency due to a lack of public healthcare coverage. Low medical card coverage rates were also found among private renters, including those who are unemployed or have a chronic illness, putting many private renters at a high financial risk in the event of a health emergency. This study discusses policies to improve equity of access to the public healthcare system through the medical card system, especially for those groups which are most vulnerable in the event of a health emergency. In particular, we discuss the expansion of universal healthcare envisioned by the 2017 Sláintecare report and potential changes to medical card eligibility thresholds.
Keywords: 330; Wohnimmobilien; Wohnungsmarkt; Gesundheitsversorgung; Gesundheitswesen; Irland